2012
DOI: 10.1039/c2cc32175k
|View full text |Cite
|
Sign up to set email alerts
|

Unique biocatalytic resolution of racemic tetrahydroberberrubine via kinetic glycosylation and enantio-selective sulfation

Abstract: In this communication, we document a facile kinetic glycosylation resolution of racemic tetrahydroberberrubine. We also demonstrate that the enantiomeric excess of the resolved products is increased via a second resolution of the minor product of the first glycosylation resolution. This provides a rare example of tandem kinetic resolution of racemates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In this study, complete β stereoselectivity and moderate diastereoselectivity were observed. Furthermore, biocatalytic glycosylation resolution of racemic tetrahydroberberrubine was reported by Yu et al 5. While our continuing efforts regarding this issue were unsuccessful, Fairbanks et al.…”
Section: Glycosylation Reaction Of 1 α and (±)‐5 Several Reaction Conmentioning
confidence: 86%
“…In this study, complete β stereoselectivity and moderate diastereoselectivity were observed. Furthermore, biocatalytic glycosylation resolution of racemic tetrahydroberberrubine was reported by Yu et al 5. While our continuing efforts regarding this issue were unsuccessful, Fairbanks et al.…”
Section: Glycosylation Reaction Of 1 α and (±)‐5 Several Reaction Conmentioning
confidence: 86%
“…[4] In this study, complete b stereoselectivity and moderate diastereoselectivity were observed. Furthermore, biocatalytic glycosylation resolution of racemic tetrahydroberberrubine was reported by Yu et al [5] While our continuing efforts regarding this issue were unsuccessful, Fairbanks et al recently reported a/bstereoselective glycosylation of a galactosyl trichloroacetimidate and chiral alcohols using a chiral Brønsted acid. [6,7] In that study, high b stereoselectivity, induced by a chiral Brønsted acid, was demonstrated.…”
mentioning
confidence: 96%
“…clearly affect the isomeric ratios obtained. 67 Similarly, the β-glycosylation of compound 8a at 32 °C with acetone as a cosolvent was found to furnish a more or less equimolar mixture of isomers, whereas a higher selectivity was observed upon incubation at 40 °C in combination with DMSO ( dr = 44/56 and 71/29, respectively). A more detailed study on the influence of reaction conditions on the enantioselectivity of transferase-catalyzed transformations has not been published yet and could thus constitute a suitable topic for prospective research.…”
Section: Resultsmentioning
confidence: 96%